Performance Of Shufflenet And Vgg-19 Architectural Classification Models For Face Recognition In Autistic Children - Melinda Melinda; Maulisa Oktiana; Yudha Nurdin; Indah Pujiati; Muhammad Irhamsyah; Nurlida Basir (INSIGHT - Indonesian Society for Knowledge and Human Development, 2024)
Indexed by Scopus/ERA